Association between adolescent lifestyle factors and high-energy traumas in early adulthood: A longitudinal study - Vaajala, Matias; Teuho, Alisa; Liukkonen, Rasmus; Ponkilainen, Ville; Rimpelä, Arja; K. Koivusilta, Leena K.; Mattila, Ville M. (Elsevier Inc., 2025)
Introduction
Longitudinal studies investigating lifestyle factors as risk factors for high-energy traumas from adolescence to adulthood are lacking. The aim of this study was to investigate the influence of 14 to 18-year old adolescent health-related behaviours, overweight, chronic disease, family socioeconomic status (SES), and adulthood education level on the risk of high-energy traumas during the average 27-year follow-up in Finland.
Materials and methods
The baseline data were surveys gathered biennially from 1981 to 1997 (the Adolescent Health and Lifestyle Survey) and individually linked with outcome data on high-energy traumas retrieved from the Care Register for Health Care until the year 2018. A logistic regression model was used to analyse the associations between the exposure variables in adolescence (frequent physical activity, overweight, smoking, monthly drunkenness, chronic disease, family SES, adulthood education level) and the overall risk for high-energy traumas. Adjusted odds ratios (aOR) with 95 % confidence intervals (CIs) were computed.
Results
A total of 876 persons (1.8 %) had a high-energy trauma during the follow-up. High-energy trauma diagnoses overall were more common among males than among females (2.8 % vs 1.0 %). Follow-up showed that those who smoked (aOR 1.49, CI 1.40–1.58), were drunk monthly (aOR 1.49, CI 1.39–1.59), had a chronic disease (aOR 1.22, CI 1.12–1.34) in adolescence or had attained only low education level in adulthood (aOR 1.39, CI 1.30–1.48) had higher odds for high-energy traumas. Frequent physical activity or overweight in adolescence were not related to the higher odds for high-energy traumas.
Conclusion
Smoking, monthly drunkenness, self-reported chronic diseases in adolescence, and low educational level in adulthood increased the risk of high-energy traumas during the mean follow-up of 27-years. Frequent physical activity and overweight in adolescence did not predict the occurrence of high-energy traumas. Intervention programs should also focus on the long-term consequences of these risk factors.
Previous article in issue